Resolving the taxonomic confusion of Taxicera Mulsant & Rey, 1873 and Dalotia Casey, 1910 (Coleoptera, Staphylinidae, Aleocharinae), with the rediscovery of Dalotia pseudorphana (Cameron, 1933), comb. nov., from bird nest material - Tasaku, Yuto; Maruyama, Munetoshi (Zootaxa, 2025)
The long-standing taxonomic confusion regarding Japanese and some Oriental species of Taxicera Mulsant & Rey, 1873 and Dalotia Casey, 1910, is resolved based on morphological studies. As a result, Dalotia garuda (Sawada, 1971), comb. nov., Dalotia pendleburyi (Cameron, 1933), comb. nov., and D. pseudorphana (Cameron, 1933), comb. nov. formerly placed in Taxicera are transferred to Dalotia. Furthermore, the rarely collected species D. pseudorphana (Cameron, 1933), comb. nov. was rediscovered in bird nesting materials.